The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/ageing/afw069
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons: Dietary protein, ageing and the Okinawan ratio

Abstract: Nutrition has profound effects on ageing and lifespan. Caloric restriction is the major nutritional intervention that historically has been shown to influence lifespan and/or healthspan in many animal models. Studies have suggested that a reduction in protein intake can also increase lifespan, albeit not as dramatically as caloric restriction. More recent research based on nutritional geometry has attempted to define the effects of nutrition on ageing over a broad landscape of dietary macronutrients and energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…The typical range for percent protein in the human diet is from 10% to 25%, with 15% to 20% being most common . It is therefore unsurprising that PL has been detected on diets with 10% but not 5% of energy from protein.…”
Section: Ten Points Of Clarificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical range for percent protein in the human diet is from 10% to 25%, with 15% to 20% being most common . It is therefore unsurprising that PL has been detected on diets with 10% but not 5% of energy from protein.…”
Section: Ten Points Of Clarificationmentioning
confidence: 99%
“…This might be the reason that some traditional low‐protein diets, such as the Mediterranean and Okinawan diets, are not associated at a population level with energy overconsumption and obesity . Along with these diets’ low protein to carbohydrate ratio, this might also explain why these diets are associated with slowed rates of aging and long life‐spans . In restricting compensatory intake for protein, the high‐fiber content of these diets is likely to limit not only nonprotein energy and total energy intake (via restricting PL) but also protein intakes, and, as discussed in the next section, dietary protein restriction is emerging as an important causal factor in studies of the effects of diet on late‐life health and lifespan .…”
Section: Ten Points Of Clarificationmentioning
confidence: 99%
“…We have already covered in the previous sections some of the differential physiological responses that distinguish CR from protein restriction (PR) and other aspects of diet composition. The impact of various feeding regimens were recently extensively reviewed (Le Couteur et al, 2016a; Le Couteur et al, 2016b; Masoro, 2005, 2006; Solon-Biet et al, 2015; Speakman and Mitchell, 2011; Speakman et al, 2016). The role of optimal dietary composition for promoting lifespan extension in ad libitum or CR condition remains unknown.…”
Section: What Role Does Dietary Composition Play?mentioning
confidence: 99%
“…However, most of the early reports in this field have suggested that manipulations of the macro and micro-nutrient composition do not have a major impact on survival (Iwasaki et al, 1988; Yu et al, 1985; Yu et al, 1982). To counter this earlier argument, a few recent studies have provided highly systematic manipulation of protein content in mouse studies (Le Couteur et al, 2016a; Le Couteur et al, 2016b; Simpson et al, 2015). For example, a 40% PR diet, while maintaining a very similar calorie intake, recapitulated the CR effects on mitochondrial ROS production and oxidative damage in rats (Ayala et al, 2007; Sanz et al, 2004).…”
Section: What Role Does Dietary Composition Play?mentioning
confidence: 99%
“…Ethnicity has also been identified as a predictor of successful ageing (4,5) . For example, people who consume diets associated with particular cultures, such as the Mediterranean and Okinawan diets, appear to have improved health outcomes and longevity (6,7) . On the negative side, older individuals tend to have suboptimal diets (8)(9)(10)(11) .…”
mentioning
confidence: 99%